STRENGTHENING THE ROLE OF THE MARKET AND FURTHER DEVELOPMENT OF ACTIVE MACROECONOMIC POLICY - Cocovic-Krstic, Mirjana (Economics of Agriculture, 2006)
In the process of transition and globalization, the creation of an efficient system of economic activities has to be based on the market- oriented economy and adequate measures of economic policy. The strengthening and enlargement of the role of the market and economic laws becomes a need all the more as the market is the best factor of valuation of all values. However, economy cannot show optimal economic results if it rests only on the market. It requires certain measures of macroeconomic policy in the field of economic activities, employment, price stability, that is, inflation and problems regarding foreign economy. The starting point for economic policy should be the market and the market effects, in the sense that it corrects or removes its randomness, adjusts the development and contributes to efficiency and rationality. Therefore, the existence of certain lavel of complementarity between the market and economic policy is very important for accomplishing development strategy, that is for rational and successful economic activities. Of the same importance is the coordination and intergration of monetarycredit and fiscal policy(.public revenue and tax policy). The instruments of economic policy, monetary and fiscal policy, are two economic disciplines, only two parts, two sub-systems of the inique financial policy. Joint activity of monetary and fiscal policy becomes a necessity – the law of modern finances. What is needed is that both policies are complementary and at the same time used with other partial policies in order to accomplish stability in the broadest sense of the word. The strategy for successful economic reforms in our economy has to be aimed at strengthening the competittion in tne market, at making more decisive steps towards market reforms, privatization administration and judicial reform, and all this in accordance with legal and administrative standards of the European Union. In other words, our economy needs new investments, a clearly-stated development strategy, more rapid growth of industrial development, new technologies and repositioning in the market in order to achieve a better position compared to our competition and more dynamuc marketing in the foreign market. The aim of all these activities is macroeconomic stability and joining the European Union.